2014
DOI: 10.4236/abb.2014.510093
|View full text |Cite
|
Sign up to set email alerts
|

Solid-State Fermentation for the Concomitant Production of δ-Endotoxin and Endospore from <i>Bacillus thuringiensis</i> subsp. <i>kurstaki</i>

Abstract: Water stress and limited aeration imparted by solid-state fermentation (SSF) were reported as crucial factors for the enhancement of endospore production by Bacillus thuringiensis (Bt); and thus, more δ-endotoxin could be produced concomitantly with reduced time. Therefore, Bt subsp. kurstaki (Btk) was employed in the present study to evaluate its efficiency for the concomitant production of endospores and δ-endotoxin in LB medium supplemented with various naturally available agricultural products, i.e., flour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Higher biomass production and induced early sporulation were achieved using several agricultural products. In addition, this process led to a reduction in the batch time for the economical production of biopesticides [161][162][163]. Zhuang et al [164] demonstrated a cost-effective production of B. thuringiensis biopesticides using a mixture of waste water sludge and wheat bran by SSF that yielded a high number of viable cells (5.98 × 10 10 CFU·g −1 ), spore counts (5.26 × 10 10 CFU·g −1 ), toxin production (7.14 mg·g −1 δ-endotoxin) and entomotoxicity (4758 IU·mg −1 ).…”
Section: Biopesticides Productionmentioning
confidence: 99%
“…Higher biomass production and induced early sporulation were achieved using several agricultural products. In addition, this process led to a reduction in the batch time for the economical production of biopesticides [161][162][163]. Zhuang et al [164] demonstrated a cost-effective production of B. thuringiensis biopesticides using a mixture of waste water sludge and wheat bran by SSF that yielded a high number of viable cells (5.98 × 10 10 CFU·g −1 ), spore counts (5.26 × 10 10 CFU·g −1 ), toxin production (7.14 mg·g −1 δ-endotoxin) and entomotoxicity (4758 IU·mg −1 ).…”
Section: Biopesticides Productionmentioning
confidence: 99%